Microsoft Internet information server 4.0 sourcebook - Petrovsky, Michele (Wiley, 1998)
This book provides a complete plan for setting up an Internet and intranet server using Microsoft's Internet Information Server. The bonus to ISS is that its free with Windows NT, and has a lot of added features that Webmasters want.